The integration effect between biochar and NPK fertilization on maize production and cob specifications under Syrian coast conditions. - عدبا, غنى; علي زيدان ,; ميس ديب, (Latakia University Journal -Biological Sciences Series, 2023)
This research was carried out in the village of Jiditi in Tartous governorate in summer season of 2021, to study the integration effect of adding three levels of biochar (B2=2%, B1=1%, B0=0%) by weight with four levels of mineral fertilizer (F3=100%, F2=75%, F1=50%. F0=0%) of the recommended fertilizer equation on production and cobs specifications of Zea mays (v, Ghouta 82), the design of the complete random blocks was adopted in this work, with three replications and 15 plants per replicate. The results showed that the addition of biochar to the soil individually had a positive effect on the cob characteristics and the grain yield of maize, but the combined effects of biochar with mineral fertilization were more significant than the individual effects of each of them separately, where the treatment B2F3 consisting of 100% of the fertilizer equation achieved with 2% Biochar has recorded the highest value of the grain yield of (10.67 tons/h), with an increase of 108% compared to the control.